BUILDING A CORPORATE SOCIAL RESPONSIBILITY MODEL FOR STATE INSTITUTIONS: A CASE STUDY OF THE JUDICIAL COMMISSION AS EXTERNAL OVERSEER OF JUDGES (DEVELOPING A CORPORATE SOCIAL RESPONSIBILITY MODEL FOR STATE INSTITUTIONS: A CASE STUDY OF THE JUDICIAL COM - Arif Budiman (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The role of external oversight institutions in maintaining the integrity of the judicial system is becoming increasingly important in contemporary governance. However, there is often a significant gap between institutional mandates and public perceptions, resulting in diminished public trust in judicial institutions. This study proposes a conceptual model of Corporate Social Responsibility (CSR) adapted from the private sector for application to the context of state institutions, using the Indonesian Judicial Commission as a comprehensive case study. Using a qualitative exploratory approach, the study analyzes the Commission's constitutional mandate in depth, combined with a review of contemporary CSR frameworks to assess its applicability to public oversight functions. The findings suggest that the adaptive application of CSR principles—such as operational transparency, authentic public participation, and sustainable community empowerment—can significantly enhance institutional legitimacy and the effectiveness of external oversight. This study introduces a CSR model tailored to the context of state institutions, comprising three key interrelated dimensions: legal education and civic awareness, public advocacy and institutional socialization, and community empowerment through participatory governance. The study suggests that CSR is not simply a tool to enhance corporate image, but a vital and strategic instrument for strengthening public trust and accountability in the modern judicial governance system.